A Study on Customer Preference and Satisfaction towards Restaurants in Coimbatore City - Yesodha Devi, N.; Kanchana, V. S. (Indian Journal of Marketing, 2009)
The present study seeks to examine the opinion of 200 respondents about their preference and satisfaction towards Restaurants. The respondents were selected by simple random sampling in Coimbatore city of Tamilnadu. The relevant data on demographic characteristics, awareness, consumption pattern, opinion on the services rendered, the factors considered in selection of the restaurants were collected with the help of a structured questionnaire. Majority of the respondents do not frequently visit the same restaurant and they are aware of the restaurants through their friends. Majority of the respondents agree and are satisfied with the services offered in the restaurants. Taste and quality are the two important factors considered in selecting a restaurant. The chi-square analysis shows that the personal factors of the respondents does not have a significant influence on the items preferred in the restaurant, and occupation has a significant influence on the occasion for visiting the restaurants. By applying ANOVA it was found that there is no significant difference among various personal factors in the level of average satisfaction score. The results of "t" test reveal that there is significant difference between the respondents "visiting the same restaurant and different restaurant" in the average satisfaction score.